Breast Implant-Associated Anaplastic Large-Cell Lymphoma in a Transgender Woman. (28th June 2017) - de Boer, Mintsje; van der Sluis, Wouter B; de Boer, Jan P; Overbeek, Lucy I H; van Leeuwen, Flora E; Rakhorst, Hinne A; van der Hulst, René R W J; Hijmering, Nathalie J; Bouman, Mark-Bram; de Jong, Daphne
Abstract: Breast implant-associated anaplastic large-cell lymphoma (BIA-ALCL) is a rare but serious complication in patients with breast implants, Patients are at risk of BIA-ALCL whether they receive breast implants for cosmetic reasons or for reconstructive purposes after surgery for breast cancer or prophylactic mastectomy. During the past decade, an increased number of reports have addressed BIA-ALCL. Herein, we describe BIA-ALCL in a transgender woman. The patient received breast implants as part of her gender transition and was diagnosed with BIA-ALCL 20 years later. The patient underwent several revisional operations in the 20 years after her primary breast surgery to treat unexplained pain with low-grade fever, severe capsular contracture (Baker grade III-IV), and several instances of implant rupture. In July 2016, the patient presented to our office with "late-onset" periprosthetic seroma 5 years after her last revisional breast surgery. She was diagnosed with BIA-ALCL without capsular invasion based on results of cytologic analysis of the periprosthetic seroma and histologic evaluation of the periprosthetic capsule. This diagnosis was verified further by results of immunohistochemical testing, which indicated expression of CD30 and T-cell markers in the periprosthetic seroma only. Our intentions with this case report are to demonstrate that all patients who undergo breast implantation, including transgender women, are at risk of BIA-ALCL and to highlight the importance of cytomorphologic and immunohistochemical screening of seroma fluid in patients with late-onset periprosthetic seroma. Level of Evidence: 5: